THE EFFECT OF MINDFULNESS BASED ON BREATHING EXERCISE ON REDUCING BLOOD PRESSURE AND BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS PATIENTS - Denis Farida; Octo Zulkarnain (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Diabetes Mellitus (DM) often involves stress-induced hypertension and glucose instability. Mindfulness-Based Breathing Exercise (MBBE) is a non-pharmacological stress management intervention designed to reduce stress responses and help stabilize blood pressure and blood glucose levels. Objective: The purpose of this study was to analyze the effect of Mindfulness Based on Breathing Exercise on reducing blood pressure and blood glucose levels in Diabetes Mellitus patients. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted at Keputih Health Center, Surabaya. Thirty respondents with Type 2 DM (aged 40-65 years, diagnosed ≥1 year, with a history) were purposively sampled into intervention (n=15) and control (n=15) groups. The intervention group practiced Mindfulness-Based Breathing Exercise for 15 minutes daily for 14 days, while the control group received standard education. Blood pressure and random blood glucose were measured using digital devices and analyzed via paired and independent t-tests. Result: The paired t-test results in the intervention group showed a significant decrease in systolic blood pressure (p=0.001), diastolic blood pressure (p=0.002), and random blood glucose levels (p=0.000). There was no significant change in the control group (p>0.05). The independent t-test results showed a significant difference in the average decrease in blood pressure and blood glucose levels between the intervention and control groups (p≤0.05). Conclusion: Mindfulness-Based Breathing Exercise significantly reduced blood pressure and blood glucose levels in patients with diabetes mellitus. This therapy is recommended as a complementary nursing intervention in the management of diabetes mellitus.